Downsizing a pharmacy library collection and meeting the information needs of clinical pharmacists in a Nigerian teaching hospital (2009)
The creation of Faculty of Pharmacy at the University of Ibadan led to the downsizing as well as the relocation of more than 80% of pharmacy books and journals from the medical library to the main campus about 15 km away from the teaching hospital/College of Medicine library, where the books were initially housed. This study revealed the hardship and problems encountered by the clinical pharmacists in the teaching hospital who were using these resources before they were relocated. The pharmacists proffered solutions to some of the problems, especially as the researcher gave them a free hand to suggest four core resources they would appreciate finding in the library. Their suggestions would guide selection of relevant resources for their use by the library. The study also determined that the study group would have gained from using the HINARI database, which the study revealed was the least used of the electronic databases available in the library, whereas the Internet was widely used as source for medical information. Though all the participants in the research claimed to be computer literate, 97% clamored for training by the librarians on information-sourcing skills.